Effect of multi-purpose tree species on chemical properties of an acid Alfisol in Meghalaya - Singh, B P; Dhyani, S K; Chauhan, D S; Prasad, R S (The Indian Journal of Agricultural Sciences, 2012)
A field investigation was initiated in 1987 at Barapani on an extremely P-deficient acid Alfisol to evaluate the multi-purpose tree species suitable for agro-forestry systems. Out of the 15 tree species studied, albizia [Periserianthesfalcataria(L.) Nielsen. syn Albizia molucama Miq.] indian alder (Alnus nepalensis D. Don), tree bean (Parkia roxburghiiG. Don) and champak(Michelia oblonga Wall. ex Hook. f. & Thoms.) were found promising for growth performance and timber volume. Different tree species intercropped with soybean [Glycine max(L.) Merr.}-linseed (Linum usitatissimum L.) sequence increased the exchangeable Ca